2014
DOI: 10.1039/c4tb01283f
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonate based organosilane modification of a simultaneously protein resistant and bioconjugable silica surface

Abstract: A facile method to coat silica surfaces with THPMP is introduced, forming simultaneously a protein resistant and bioconjugable surface.The coating is experimentally identified and its anti-fouling and bioconjugable characteristics are demonstrated.Chemical modication of surfaces, which enables unprecedented manipulation of the characteristics of materials, can be attained by a virtually indenite number of different compounds and methods. Regarding the accommodation of molecules over surfaces, self-assembly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…The C 1s scan of an APTES/TMMS coated microtoroid showed three peaks located at 286, 285, and 284 eV verifying C−N, 31 C−C 32 and C−H, 32 and C−Si 33 bondings, respectively, due to covalent bonding of APTES/TMMS molecules ( Figure S7). Also, the O 1s peak located at 530.5 eV 34 and the increase in intensity of the higher energy Si 2p peak after coating, verifies the Si−O bonding. 35 N 1s scan showed two peaks at 401.6 and 399.2 eV arising from protonated amine (−NH 3 + ) and free amine (−NH 2 ) groups 36,32 due to covalent conjugation of APTES molecules, respectively.…”
Section: Analytical Chemistrymentioning
confidence: 93%
“…The C 1s scan of an APTES/TMMS coated microtoroid showed three peaks located at 286, 285, and 284 eV verifying C−N, 31 C−C 32 and C−H, 32 and C−Si 33 bondings, respectively, due to covalent bonding of APTES/TMMS molecules ( Figure S7). Also, the O 1s peak located at 530.5 eV 34 and the increase in intensity of the higher energy Si 2p peak after coating, verifies the Si−O bonding. 35 N 1s scan showed two peaks at 401.6 and 399.2 eV arising from protonated amine (−NH 3 + ) and free amine (−NH 2 ) groups 36,32 due to covalent conjugation of APTES molecules, respectively.…”
Section: Analytical Chemistrymentioning
confidence: 93%
“…Recently, we have suggested that coating of an organosilane molecule having methylphosphonate functional group could be used to form a simultaneously protein resistant and bioconjugable silica surface 24 . In this article, we demonstrate, for the first time, that this multifunctional coating could indeed solve the aforementioned problem of biosensing with the WGM microresonators by enabling recognition of antigens after functionalization of microtoroids with corresponding antibodies with high sensitivity in complex media and also by suppressing non-specific interactions simultaneously.…”
mentioning
confidence: 99%
“…The Q measured here is 3.95 × 10 6 . Microtoroids were first coated with 3-(Trihydroxysilyl) propyl methylphosphonate (THPMP), which forms an anti-fouling layer over silica surfaces, using a slightly modified recipe than we used in our previous research 24 (Methods). Piranha cleaned and THPMP coated microtoroids were compared regarding non-specific adsorption of albumin–fluorescein isothiocyanate conjugate (FITC-BSA) by confocal microscopy.…”
mentioning
confidence: 99%
“…The R q value for the bare SiO 2 surface was obtained as 0.45 nm, in agreement with our previous report. 35 The corresponding line profile of the 2D image, shown with a blue line, was given in Figure 1F, demonstrating a smooth SiO 2 surface. As can be seen in the 3D AFM image of the α-Exotoxin A functionalized surface ( Figure 1E) and in the corresponding line profile (Figure 1G), the surface roughness was increased apparently and the R q value was calculated as 1.24 nm.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…One strategy for eliminating such lower spectral shifts is by creating biointerfaces which suppress only the nonspecific interactions, while not interfering with the biodetection ability. As a step forward in achieving this task, we previously demonstrated a surface modification approach, using 3-(trihydroxysilyl) propyl methylphosphonate (THPMP) molecules, 35 for selective human interleukin 2 antigen sensing in a diluted fetal bovine serum. 36 In this study, using the same surface modification approach, we performed optical biodetection of Pseudomonas aeruginosa exotoxin A in a diluted artificial sputum medium, prepared by mimicking the respiratory environment of Cystic Fibrosis (CF) patients.…”
mentioning
confidence: 99%